2010 22nd International Conference on Indium Phosphide and Related Materials (IPRM) 2010
DOI: 10.1109/iciprm.2010.5515966
|View full text |Cite
|
Sign up to set email alerts
|

Reliability study on InP/InGaAs emitter-base junction for high-speed and low-power InP HBT

Abstract: The reliability of sub-micrometers InP-based heterostructure bipolar transistors (HBTs), which are being applied in over-100-Gbit/s ICs, was examined at high current injection conditions. These HBTs had a ledge structure and an emitter electrode consisting with a refractory metal of W, which suppressed surface degradation and metal diffusion, respectively. We conducted bias-temperature (BT) stress tests in several stress conditions of current densities, J c , up to 10 mA/μm 2 in order to investigate the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results indicate that the device failure under electro-thermal stress is mainly due to the traps introduced at the emitter-sidewall/passivation interface, the B-E junction, and the increase in the emitter resistance. Y. K. Fukai et al studied the reliability of submicrometer, high-speed and low-power InP HBTs with a 0.6 × 3 µm 2 emitter size at high current densities [12], and pointed out that the degradation of the B-E junction is the main factor leading to the failure of devices under high current densities. Hong Wang et al reported the reliability of InGaAs/InP DHBTs with two different emitters areas (emitter area of 5 × 20 µm 2 and 40 × 40 µm 2 ) under a high reverse B-C bias voltage (avalanche) regime [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the device failure under electro-thermal stress is mainly due to the traps introduced at the emitter-sidewall/passivation interface, the B-E junction, and the increase in the emitter resistance. Y. K. Fukai et al studied the reliability of submicrometer, high-speed and low-power InP HBTs with a 0.6 × 3 µm 2 emitter size at high current densities [12], and pointed out that the degradation of the B-E junction is the main factor leading to the failure of devices under high current densities. Hong Wang et al reported the reliability of InGaAs/InP DHBTs with two different emitters areas (emitter area of 5 × 20 µm 2 and 40 × 40 µm 2 ) under a high reverse B-C bias voltage (avalanche) regime [13].…”
Section: Introductionmentioning
confidence: 99%